Changing Risk Factors in Patients Diagnosed with Human Immunodeficiency Virus - Sula Frausto; Heather Sperring; Glorimar Ruiz-Mercado; Cassandra Pierre; Kathryn Scrudder; Ijeoma Okafor; Kerrie Nelson; Elissa M Schechter-Perkins (Western Journal of Emergency Medicine, 2026)
Introduction: Since 2019, transmission risk factors among patients diagnosed with HIV have changed, although the trends and reasons behind them have not been fully elucidated. The objective of this study was to assess changes in HIV transmission risk factors among patients newly diagnosed with HIV to inform future targeted HIV testing programs. Methods: This study site is New England’s largest essential hospital and a major reporter of new HIV cases in Massachusetts. We performed a retrospective chart review of patients diagnosed with HIV infection at our medical center between January 2019 and December 2023. Demographic and clinical variables were collected and analyzed using descriptive and comparative statistics to evaluate trends in primary risk factor for HIV. Our primary outcome measure was incident HIV diagnosis with a primary risk factor of injection drug use (IDU), men who have sex with men (MSM), or heterosexual contact. A secondary outcome examined was CD4 count at the time of diagnosis. Results: A total of 246 patients were newly diagnosed with HIV. Of these, 59% (n = 146) reported heterosexual contact as their most likely cause of transmission, 19% (n = 47) MSM, 19% IDU (n = 46), and 3% (n = 7) reported both MSM and IDU. Heterosexual contact increased as the predominant HIV transmission factor from 53% (24/45) in 2019 to 79% (37/47) in 2023 (risk difference, 25%; 95% CI, 6.7%-44.1%), and the percentage of diagnoses made in non-US-born patients increased from 60% (27/45) in 2019 to 83% (39/47) in 2023 (risk difference, 23%; 95% CI, 5.1%-41%). Non-US born patients had significantly lower CD4 counts at diagnosis (mean [SD] CD4 count 299 [241] cells/µL) compared to US-born counterparts (mean [SD] CD4 count 498 [309] cells/µL, P < .001), with a mean difference of -199 cells/µL (95% CI, -272 to -125). Conclusion: The dominant risk factor for HIV transmission has changed from injection drug use/men who have sex with men to heterosexual contact in New England’s largest city. Our findings associate increased HIV incidence in non-US-born immigrants at an urban essential hospital, highlighting the importance of considering this group in targeted public health efforts to avoid missing cases of HIV in similar settings.